2021
DOI: 10.2139/ssrn.3766490
|View full text |Cite
|
Sign up to set email alerts
|

Disassembly and Rewiring of a Mature Converging Excitatory Circuit Following Injury

Abstract: Specificity and timing of synapse disassembly in the CNS are essential to learning how individual circuits react to neurodegeneration of the postsynaptic neuron. In sensory systems such as the mammalian retina, synaptic connections of second-order neurons are known to remodel and reconnect in the face of sensory cell loss. Here we analyzed whether degenerating third-order neurons can remodel their local presynaptic connectivity. We injured adult retinal ganglion cells by transiently elevating intraocular press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In addition, other authors have characterized the presence of calbindin expressed in ONs-αRGCs (in addition to the labeling of a subpopulation of amacrine cells; Krieger et al, 2017;Sonoda et al, 2020) which, when colocalized with an αRGC pan-marker, allows for reliable detection of ONs-αRGCs. Previous studies have documented that these M4-ipRGCs (ONs-αRGCs) are 10.3389/fnana.2022.1054849 more resistant to retinal injury (El-Danaf and Huberman, 2015;Ou et al, 2016;Tran et al, 2019), due to their ability to alter their synaptic connectivity pattern after injury to promote survival (Della Santina et al, 2021). However, there is not a complete consensus on this characteristic, as in other studies, M4-ipRGCs have not been more resistant than the rest of the RGCs (Gallego-Ortega et al, 2021;Gao et al, 2022), reviewed in Tran et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other authors have characterized the presence of calbindin expressed in ONs-αRGCs (in addition to the labeling of a subpopulation of amacrine cells; Krieger et al, 2017;Sonoda et al, 2020) which, when colocalized with an αRGC pan-marker, allows for reliable detection of ONs-αRGCs. Previous studies have documented that these M4-ipRGCs (ONs-αRGCs) are 10.3389/fnana.2022.1054849 more resistant to retinal injury (El-Danaf and Huberman, 2015;Ou et al, 2016;Tran et al, 2019), due to their ability to alter their synaptic connectivity pattern after injury to promote survival (Della Santina et al, 2021). However, there is not a complete consensus on this characteristic, as in other studies, M4-ipRGCs have not been more resistant than the rest of the RGCs (Gallego-Ortega et al, 2021;Gao et al, 2022), reviewed in Tran et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…In loop-induced 46,47 and microspheres-induced ocular hypertensive models 48 , an increase in ERG signal has been described as a reflection of synaptic imbalance at the onset of intraocular pressure increase. And a recent study demonstrated a structural plasticity with increased synaptic connectivity with rods while undergoing glaucoma degeneration 49 . This hyperactivity may be one of the earliest dysfunctions of the pathophysiological process of neurodegeneration 50 (suggested in other neurodegenerative diseases such as Alzheimer's disease 51 or multiple sclerosis 52 ).…”
Section: Discussionmentioning
confidence: 99%